Slow pyrolysis of an LDPE/PP mixture: Kinetics and process performance. (June 2021) - Maniscalco, Marco; La Paglia, Fabiola; Iannotta, Pasquale; Caputo, Giuseppe; Scargiali, Francesca; Grisafi, Franco; Brucato, Alberto
Abstract: High- and low-density polyethylene (HDPE and LDPE) and polypropylene (PP) are the most common polymers among plastic waste as they have multiple commercial applications. This study focused on thermal degradation characteristics and kinetic of a plastic mixture with a composition of 92.5 wt% LDPE and 7.5% PP. Thermal decomposition characteristics of the plastic mixture was analysed through thermo-gravimetric analysis (TGA). The overall kinetic of the process was studied using the modified Coats−Redfern method and the Ozawa-Flynn-Wall (OFW) method. The apparent activation energy (E) and pre-exponential factor (A) obtained were 316.0 kJ/mol; 8.09E+21 min −1 and 311.5 kJ/mol; 4.35E+21 min −1, respectively. Slow pyrolysis of the analysed mixture was carried out in a semi-batch reactor under atmospheric pressure and nitrogen atmosphere and three different pyrolysis temperatures were investigated: 420 °C, 450 °C and 500 °C. H2, CH4, C2 H4, C2 H6 and C3 H8 were the main components of the gas phase. Liquid (oil/wax phase) yields increased with increasing operative temperature from 42% at 420 °C to 62% at 500 °C. On the other hand, solid phase showed a specular behaviour compared to the oil/wax phase, decreasing from 21% to 5% in the considered temperature range. On the contrary, gas phase did not change much with pyrolysis temperature, with a decrease from 37% at 420 °C to 34% at 500 °C. Products' energy yields were also estimated at 420 °C. They ranged from 7.4% to 37.8% and 43.0% for solid, gas and oil fraction, respectively. Oil fraction collected from pyrolysis at 420 °C was also characterized. Highlights: Liquid yields increased with temperature from 42% at 420 °C to 62% at 500 °C. Oil/wax phase properties and aspect showed significant variations with temperature. Gas yield is maximum at 420 °C and slightly decreased with increasing temperature. Produced liquid phase was mostly composed of aliphatic compounds. At 420 °C most of the mixture initial energy content was divided between oil and gas fractions.